2021
DOI: 10.1177/1090198120988252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a School-Based Child Physical and Sexual Abuse Prevention Program

Abstract: Background Evidence-based child sexual and physical abuse prevention programs delivered in schools are needed and require rigorous evaluation of program effects prior to widespread dissemination. The Play it Safe! program is a one-time session delivered by trained facilitators to teach students about recognizing, resisting, and reporting abuse. Aims To evaluate a school-based child sexual and physical abuse prevention intervention Play it Safe! among elementary school students using a cluster randomized design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The above-mentioned fears and concerns highlight the need for services by professionals and related organizations, as they are responsible for dealing with child abuse and child and parent support activities. In addition to social work services, professional interventions are needed to empower children and their parents before child sexual abuse occurs since a review of studies has shown that these interventions play a vital role in disclosing sexual harassment and reducing the prevalence of child sexual abuse and its consequences (18)(19)(20)(21)(22)32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above-mentioned fears and concerns highlight the need for services by professionals and related organizations, as they are responsible for dealing with child abuse and child and parent support activities. In addition to social work services, professional interventions are needed to empower children and their parents before child sexual abuse occurs since a review of studies has shown that these interventions play a vital role in disclosing sexual harassment and reducing the prevalence of child sexual abuse and its consequences (18)(19)(20)(21)(22)32).…”
Section: Discussionmentioning
confidence: 99%
“…Various international studies have been conducted to prevent the first level of child abuse in preschool and elementary school children, including educational interventions, increasing targeted skills of saying no, shouting and disclosing child abuse through educational programs, playing doll roles, watching theaters and films by par-ents and professionals (e.g., teachers and the police), and through knowledge and raising awareness of body ownership. These interventions are believed to increase children's knowledge and awareness to enable them to protect themselves against child abuse (18)(19)(20)(21)(22). To the best of our knowledge, no study has yet evaluated child sexual abuse interventions in Iran.…”
mentioning
confidence: 99%
“…Kenny et al's (2022) later evaluation of the same programme consisted of pre‐ and post‐tests consisting of five safety rules applied to different items (statements) which varied by grade, although again neglect was not included. Thompson et al (2022) conducted a randomised control trial of the Play it Safe! programme which targets sexual and physical abuse for elementary school children.…”
Section: Introductionmentioning
confidence: 99%